INTERNATIONAL MANAGEMENT INTRODUCTION - Bolbekova Ug'iloy Jaloliddinovna; Rajabov Ma’ruf Normurodovich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article explores the concept of International Management and its  growing  importance  in  today’s  globalized  economy.  International  management refers  to  the  process  of  planning,  organizing,  leading,  and  controlling  business operations across national borders. The study highlights key aspects such as cultural diversity, global leadership, international strategy, and cross-border communication. It also  examines  the  challenges  faced  by  managers  in  multinational  environments, including differences in legal systems, economic conditions, and cultural values.